ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI LAMA MENCARI KERJA BAGI TENAGA KERJA TERDIDIK DI KOTA AMBON - Indrayady Lumapelumey (Jurnal Cita Ekonomika, 2019)
The purpose of this study was to know the effect of age, length of study and skills of tertiary graduates in Ambon, and to know the length of time they need to get a job. The research method is quantitative descriptive using primary data, which is a questionnaire. Method data analysis is descriptive analysis and multiple linear regression with OLS (Ordinary Least Square) method. And for The partial test the writer use the t-statistic test. In addition, a classic assumption test is performed, where all testing uses tools such as the SPSS 20 program. The results of this study were the age variable has a positive and significant effect on the length of work seeking, the skills variable has a positive and significant effect on the length of work search, and the last is time variable which is how long the job seekers need to finish their study has a positive and significant effect on the length of work search.